Deciphering the Role of microRNAs in Regulation of Immune Surveillance, Self-Tolerance and Allograft Transplant Outcome - Leung, Cherry S.; Lu, Song; Li, Jiatao; Wu, William K.; Lui, Kathy O. (Current Stem Cell Research & Therapy, 2018)
MicroRNAs are small non-coding RNAs that can modulate gene expression at posttranscriptional level, and they participate in almost all important biological processes. Immune system is elaborately regulated to maintain the equilibrium between immunity and tolerance. Recent studies have revealed significant functions of microRNAs in the maintenance of immune homeostasis using both cell and transgenic mouse models. In collaboration with various transcriptional factors and cytokines, microRNAs constitute an effective and flexible regulatory network governing the development and activation of immune cells; as well as maintenance of immune tolerance. In this review, microRNAs involved in T cell development, proliferation, and lineage differentiation will be summarized. Based on current knowledge, the function of microRNAs in establishing and maintaining immune tolerance will also be discussed in relation to determining the outcome of allograft transplantation.
Keywords: gene regulation